Efektivitas Massage Edorphin Terhadap Kecemasan Ibu Hamil dalam Menghadapi Persalinan di Klinik Azzahra Maja Kabupaten Lebak Banten Tahun 2023 - Endah Rahayu; Maryati Sutarno (Universitas Malahayati Lampung, 2024)
ABSTRACT Anxiety for pregnant women is a psychological problem that continues when facing labor so that it causes difficulties and length of labor and will be at risk of maternal death. Endorphin massage is one way to reduce anxiety by eliminating fatigue in the body and creating a sense of comfort. Knowing the effectiveness of endorphin massage on the anxiety of pregnant women in facing childbirth at the Azzahra Maja Clinic, Lebak Regency, Banten. Quasy experimental research using a pretest-posttest control group design. The sample in this study were pregnant women with a gestational age 36 weeks at the Azzahra Maja Clinic, Lebak Banten Regency in January, totaling 50 people using the accidental sampling technique. Data were analyzed using Mann Whitney which had previously been tested for normality and homogeneity. Univariate analysis of anxiety in the intervention group with an average anxiety of 27.88 and thereafter with an average anxiety of 14.17. Anxiety in the control group at examination I with an average anxiety of 24.08, on examination II with an average anxiety of 19.21%. The results of the bivariate analysis found that giving endorphin massage to the anxiety of pregnant women in facing labor with a significance value of 0.008. Endorphin massage is effective against pregnant women's anxiety in facing labor. It is expected that pregnant women who experience anxiety should do endorphin massage to reduce anxiety so that they can reduce the use of pharmacological therapy by doing massage on the right and left back in a V shape for 30 minutes so that the mother feels relaxed. Keywords: Endorphin Massage, Anxiety of Pregnant Women in Facing Labor ABSTRAK Kecemasan ibu hamil merupakan permasalahan psikologis yang berlanjut saat menghadapi persalinan sehinnga menimbulkan kesulitan dan lamanya persalinan serta akan beresiko pada kematian ibu. Massage endorphin merupakan salah satu cara untuk menurunkan kecemasan dengan cara menghilangkan rasa lelah pada tubuh dan menciptakan rasa nyaman. Mengetahui efektivitas massage endorphin terhadap kecemasan ibu hamil dalam menghadapi persalinan di Klinik Azzahra Maja Kabupaten Lebak Banten. Penelitian quasy experimental menggunakan rancangan pretest-posttest control group design. Sampel dalam penelitian ini ibu hamil dengan usia kehamilan 36 minggu Klinik Azzahra Maja Kabupaten Lebak Banten pada bulan Januari berjumlah 50 orang dengan teknik accidentaly sampling. Data dianalisis menggunakan Mann Whitney yang sebelumnya dilakukan uji normalitas dan homogenitas. Analisis univariat kecemasan pada kelompok intervensi dengan rata-rata kecemasan 27,88 dan sesudahnya dengan rata-rata kecemasan 14,17. Kecemasan pada kelompok kontrol pada pemeriksaan I dengan rata-rata kecemasan 24,08, pada pemeriksaan II dengan rata-rata kecemasan 19,21%. Hasil analisis bivariat terdapat pemberian massage endorphin terhadap kecemasan ibu hamil dalam menghadapi persalinan dengan nilai sigifikansi 0,008. Massage endorphin efektif terhadap kecemasan ibu hamil dalam menghadapi persalinan. Diharapkan ibu hamil yang mengalami kecemasan hendaknya melakukan massage endorphin untuk mengurangi kecemasan sehingga dapat mengurangi penggunaan terapi farmakologis dengan cara melakukan pijat pada bagian punggung kanan dan kiri dengan bentuk V selama 30 menit sehingga ibu merasa rileks. Kata Kunci: Massage Endorphin, Kecemasan Ibu Hamil dalam Menghadapi Persalinan